Ichthyotoxic principles against zebrafish embryos from the Indonesian marine sponge Neopetrosia chaliniformis - Novriyandi Hanif, Resi Ardianti, Peni Ahmadi, Andi Setiawan & , Kusdiantoro Mohamad, Nicole J. de Voogd, Anggia Murni, Junichi Tanaka (Journal of Applied Pharmaceutical Science, 2018)
Endophytic the chemical ecology of Neopetrosia chaliniformis has never been studied before. A study on the extract of the Indonesian marine sponge N. chaliniformis for the ichthyotoxicity including its teratogenic effect against zebrafish (Danio rerio) embryos led to the identification of oxaquinolizidine alkaloids araguspongines C (1) and D (2). Their structure and conformation were determined on the basis of spectroscopic method and molecular modeling analysis. The ichthyotoxicity araguspongines fraction against zebrafish embryos showed LC50 4.3 μg/ml (death, 48-hours post fertilization (hpf)) and 3.6 μg/ml (death, 72 hpf) as well as observation of its teratogenic effects including death, coagulation egg, tail, notochord, heart malformation, and yolk-sac edema at 24, 48, and 72 hpf. Because 76% cell death malformations in zebrafish embryos was observed, araguspongine rich fraction may serve as antimitotic-like drug in the treatment of cancer.
Keywords: Oxaquinolizidine,Neopetrosia chaliniformis,NMR,molecular modeling,zebrafish embryos.